Digital risk perception among middle-aged and older adults in China: a perspective from mobile phone dependence within the I-PACE model - Lu, Ying; Zhang, Rou; Dai, Weihui (Frontiers in Psychiatry, 2026)
IntroductionThe digital inclusion of middle-aged and older adults, while socially beneficial, exposes this population with relatively lower digital literacy to increased cybersecurity risks. However, the current understanding of the psychosocial mechanisms that undermine their digital risk perception (DRP) remains fragmented.MethodsGrounded in the Interaction of Person-Affect-Cognition-Execution (I-PACE) model, this study explored the interrelations among key psychological and behavioral factors associated with DRP. Data from 356 Chinese middle-aged and older adults aged 45 years and above in Chongqing were analyzed using structural equation modeling (SEM) combined with regression-based SHAP analysis.ResultsMobile phone dependence (MPD) was negatively associated with DRP (b = -0.253, p < 0.001). Loneliness and low perceived social support were correlated with greater fear of missing out (FoMO) and higher MPD, which were in turn linked to lower DRP. The findings also revealed a correlational pattern suggesting bidirectional tendencies between MPD and FoMO. The SHAP interpretation indicated that loneliness was the strongest correlate of DRP, followed by MPD and FoMO.DiscussionThe identified pattern aligns with the process logic of the I-PACE framework. Overall, the study delineates an integrated pattern of psychological and behavioral factors influencing DRP and provides a conceptual basis for strengthening digital safety awareness and literacy among middle-aged and older adults.